Employees’ voluntary green behavior in small and medium-sized tourism enterprises – a case study of Hanoi - Minh, Nguyen Ngoc (Edelweiss Applied Science and Technology, 2025)
With sustainable development becoming a strategic priority, green inclusive leadership plays a vital role in encouraging environmentally conscious behavior among employees across various sectors. However, research on green behavior and green inclusive leadership remains limited. Based on social identity theory and upper echelons theory, this study examines the impacts of green inclusive leadership, green commitment, and green organizational identity on employees’ voluntary green behaviors. Data were collected from 315 employees working in small and medium-sized tourism enterprises in Hanoi City. Using quantitative analysis techniques, including Cronbach’s Alpha, exploratory factor analysis (EFA), correlation analysis, and linear regression analysis. The results show that green inclusive leadership, green commitment, and green organizational identity have a significant and positive impact on employees’ voluntary green behavior. Additionally, green inclusive leadership is found to influence green organizational identity and green commitment positively. This finding not only fills a theoretical gap in the field of green leadership and behavior but also offers practical implications for small- and medium-sized tourism enterprises, including developing a green organizational culture, boosting employee engagement, and advancing sustainable development.